Constitutional Democracy and National Legal Instruments in Resolving Regional Election Disputes - Tanjung, Muhammad Anwar Tanjung; Saraswati, Retno; Tyesta A.L.W, Lita (APPTHI, 2020)
Through Law Number 32 of 2004 concerning Regional Government, direct regional head elections (Pemilihan Umum Kepala Daerah/Pilkada) could finally be realized. In accordance with the mandate of Article 24C paragraph (1) of the 1945 Constitution, it stipulates that one of the powers of the Constitutional Court is to decide disputes over election results, which means that this includes post-conflict local election disputes. In this context, the Constitutional Court performs its role to maintain the constitutional democracy adopted in Indonesian legal system fo resolve election disputes. Upholding the constitution is a form of protecting the constitutional rights of citizens and is a consequence of the adherence to the notion of constitutionalism that the 1945 Constitution. In this context, the constitution becomes a living constitution in the life of the nation and state. Constitutional values and norms will always be alive in the sense that they are constantly developing and enriched with new values and systems based on the practice of the constitution itself and real experiences in everyday life. To maintain the election process in order to achieve the expected results, it cannot rely on only one or two institutions. It requires the cooperation of all state organs, including KPU, Bawaslu, DKPP, police, prosecutors, courts, and the Constitutional Court. All these state organs must work together to make the local elections a success to maintain the sovereignty of the people.